Teoria de arte portuguesa nos escritos de artistas plásticos dos anos 60 - Rito, Paula Alexandra Miranda (2000)
The subject of this research is centered on essays by portuguese artists of the 60’s., analysed on a basis of correspondence, searching for contributions on how to avaluate questions or subjectmatters in art theories. Being aware of the complexity of the art commitments involved in the assumed opposition” Abstractedness vs. Figurativeness”, these authors reflected upon the history, the aesthetics, the criticism and the vanguardism on question at the time. In the interconnection between the cultural, social and political fields there was a clear predominance of the last, within the portuguese political system, wich influenced directly and also indirectly the artistic milieu. By bringing into question such topics as aesthetics autonomy and formalization as well as those of the interpretation